Pengaruh Profitabilitas dan Leverage Terhadap Kebijakan Dividen dengan Likuiditas Sebagai Variabel Moderasi Pada Perusahaan Badan Usaha Milik Negara (BUMN) Tahun 2020–2023 - Maharani, Annisa Citra; Valdiansyah, Riyan Harbi (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2025)
This research examines how profitability and leverage affect dividend policy with liquidity as a moderation variable. This research took a sample of Indonesian State-Owned Enterprises for the 2020-2023, especially those that have conducted an IPO (Initial Public Offering). This research uses E-Views 13 for logistic regression analysis. The secondary data, financial reports are collected through the website provided by each sample company. This research found that profitability and leverage negatively significantly affected dividend policy, liquidity successfully moderated the relationship between profitability and dividend policy, but failed to moderate the relationship between leverage and dividend policy. Therefore, the researcher's advice for investors is to analyze leverage as a consideration in investing in stocks, because leverage can affect dividend policy as well as analyze liquidity ratios that can strengthen other factors in influencing dividend policy. Then, this study uses dummy variables in proxying dividend policy so that researchers recommend that further research use other variables and proxies to obtain different results.